2013
DOI: 10.1590/s1517-83822013000300016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the PetrifilmTM EB and TEMPO® EB systems with ISO 21528-2:2004 method for the count of Enterobacteriaceae in milk

Abstract: The development of alternative microbiological techniques is driven by the necessity to meet the current needs to deliver rapid results in the manufacturing process of foods, but it is important that these methods be evaluated for each application. The objective of the present study was to assess the Petrifilm™ EB and the TEMPO® EB systems with ISO 21528-2:2004 for the count of Enterobacteriaceae in pasteurized and UHT milk samples. We analyzed the microflora of 141 pasteurized milk samples, 15 samples of arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous comparison studies of TEMPO ® system for examinations of different microbiological parameters (total viable count, coliforms, E. coli count) in various food matrices also showed high correlation with the respective reference methods [2,3,[13][14][15]. As an example, Zitz et al [16] evaluated three TEMPO ® applications to enumerate total viable count, total coliforms and E. coli in milk and soft fresh cheeses and found that the TEMPO ® methods showed equal or better precision and, for some parameters, higher recovery compared to the traditional MPN-based methods.…”
Section: Biomerieux Has Obtained Afnor Validation For the Tempomentioning
confidence: 86%
See 1 more Smart Citation
“…Previous comparison studies of TEMPO ® system for examinations of different microbiological parameters (total viable count, coliforms, E. coli count) in various food matrices also showed high correlation with the respective reference methods [2,3,[13][14][15]. As an example, Zitz et al [16] evaluated three TEMPO ® applications to enumerate total viable count, total coliforms and E. coli in milk and soft fresh cheeses and found that the TEMPO ® methods showed equal or better precision and, for some parameters, higher recovery compared to the traditional MPN-based methods.…”
Section: Biomerieux Has Obtained Afnor Validation For the Tempomentioning
confidence: 86%
“…Of these, Enterobacteriaceae is usually tested as a hygiene indicator intended to verify the hygiene programs applied at the production premises [2,3].…”
mentioning
confidence: 99%